CEOs' temporal focus, firm strategic change, and performance: Insights from a paradox perspective. Issue 6 (December 2020) - Back, Pascal; Rosing, Kathrin; Dickler, Teresa Antonia; Kraft, Priscilla Sarai; Bausch, Andreas
Abstract: Recent research indicates that CEOs' temporal focus (the degree to which individuals attend to the past, present, and future) is a critical predictor for strategic outcomes. Building on paradox theory and the attention-based view, we examine the implications of CEOs' past and future focus for strategic change. Results from polynomial regression analysis reveal that CEOs who cognitively embrace both the past and the future at the same time engage more in strategic change. In addition, our results reveal that the positive strategic change−firm performance relationship is enhanced when CEOs' past focus is high, whereas CEOs' future focus mitigates the translation of strategic change into firm performance (when their past focus is low at the same time). In addition, supplemental analyses indicate that the impact of CEOs' temporal focus turns out differently in stable and dynamic environments. Our study thus extends the literature on both individual's temporal focus and strategic change.